2013
DOI: 10.1098/rsif.2013.0605
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and inference reveal nonlinear length-dependent suppression of somatic instability for small disease associated alleles in myotonic dystrophy type 1 and Huntington disease

Abstract: More than 20 human genetic diseases are associated with inheriting an unstable expanded DNA simple sequence tandem repeat, for example, CTG (cytosinethymine-guanine) repeats in myotonic dystrophy type 1 (DM1) and CAG (cytosine-adenine-guanine) repeats in Huntington disease (HD). These sequences mutate by changing the number of repeats not just between generations, but also during the lifetime of affected individuals. Levels of somatic instability contribute to disease onset and progression but as changes are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 42 publications
3
19
0
Order By: Relevance
“…Similarly, in R6/2 mice inheriting the large alleles (N500 repeats), it seems likely that the high levels of variance observed within tissues with two populations of cells diverging in average repeat length are generated by frequent expansions and contractions in both cell populations, but with the relative balance between expansions and contractions subtly reversed. Mathematical modeling of repeat length variation also revealed evidence for a non-linear allele length-dependent increase in the contraction frequency over a similar range of allele lengths Higham and Monckton, 2013) and is entirely consistent with the repeat dynamics observed here in R6/2 mice. Interestingly, data from intergenerational transmissions and direct sperm analyses in DM1 also reveal both a decreasing expansion rate and increasing contraction frequency with increasing allele length (Ashizawa et al, 1994;Fig.…”
Section: Tablesupporting
confidence: 82%
See 2 more Smart Citations
“…Similarly, in R6/2 mice inheriting the large alleles (N500 repeats), it seems likely that the high levels of variance observed within tissues with two populations of cells diverging in average repeat length are generated by frequent expansions and contractions in both cell populations, but with the relative balance between expansions and contractions subtly reversed. Mathematical modeling of repeat length variation also revealed evidence for a non-linear allele length-dependent increase in the contraction frequency over a similar range of allele lengths Higham and Monckton, 2013) and is entirely consistent with the repeat dynamics observed here in R6/2 mice. Interestingly, data from intergenerational transmissions and direct sperm analyses in DM1 also reveal both a decreasing expansion rate and increasing contraction frequency with increasing allele length (Ashizawa et al, 1994;Fig.…”
Section: Tablesupporting
confidence: 82%
“…In HD mouse models deficient for either Msh2 or Msh3 mismatch repair genes, somatic mosaicism is completely suppressed with neither expansions nor contractions accumulating (Manley et al, 1999;Wheeler et al, 2003;Dragileva et al, 2009). Similarly, individual-specific expansion and contraction frequencies are highly correlated with each other in HD and DM1 patients Higham and Monckton, 2013). These observations argue for one major mutational pathway in which expansions and contractions are alternative outcomes of the same underlying process (Gomes-Pereira et al, 2004b).…”
Section: Tablementioning
confidence: 94%
See 1 more Smart Citation
“…This is consistent with the behavior of CAG repeats at both the HD and androgen receptor loci in humans (Zhang et al 1994;Leeflang et al 1995). Recent work modeling human DM1 expansion data also has demonstrated that these expansions are likely to occur through small incremental steps Morales et al 2012;Higham and Monckton 2013). In induced pluripotent stem cells (iPSCs) from HD and DM1 patients, Du et al (2013) observed that (CAG) $46 and (CTG) $57 tracts were stable after 12 and 16 passages, respectively.…”
Section: Discussionsupporting
confidence: 52%
“…Studies of TNR tract length changes have largely relied on end point experiments and therefore do not address the dynamic behavior of the tracts, i.e., the rate at which tracts continue to expand. Modeling of human data has predicted that threshold-length TNR tracts will continue to increase in length in increments smaller than the repeat itself Morales et al 2012;Higham and Monckton 2013), although this has never been demonstrated directly. Single-sperm typing studies in humans demonstrated small expansion and contraction events (one-two repeats) in TNR sequences in Kennedy's disease, HD, and DM1 patients (Zhang et al 1994;Leeflang et al 1995Leeflang et al , 1999Martorell et al 2004), particularly in alleles near the pathogenic threshold (Zhang et al 1994;Leeflang et al 1995;Castel et al 2010).…”
mentioning
confidence: 99%